A 28 GHz GaN HEMT quasi‐circulator with high isolation and high power‐handling capability. Issue 1 (15th September 2021) - Wang, Xiyao; Cai, Qi; Zhu, Haoshen; Feng, Wenjie; Xue, Quan; Che, Wenquan
Abstract: An active quasi‐circulator using gallium nitride (GaN) high electron mobility transistors technology is presented. By using two common‐gate and one common‐source transistors, two self‐interference signal paths from transmitting (Tx)‐port to receiving (Rx)‐port are constructed. Due to the features of out‐of‐phase and equal magnitude for the two‐path signals, sufficient Tx‐Rx isolation can be realized through cancellation of the two‐path signals at the Rx‐port. One prototype working at 27–29 GHz was designed and fabricated for demonstration. The measured results indicate maximum isolation of 44 dB at 28.2 GHz and the 30 dB isolation bandwidth of 300 MHz. The measured insertion losses of Tx‐path and Rx‐path are less than 4.5 and 3.6 dB within the operating frequency. Due to the high power density of the GaN devices, the measured IP1dB of the quasi‐circulator is better than 18 dBm.